Sprouting of chayote (Sechium edule (Jacq.) Sw.) as influenced by various postharvest treatments - Bayogan, Emma Ruth V.; Secretaria, Leizel B.; Lubaton, Christine Diana S.; Photchanachai, Songsin (2019)
Chayote, a gourd which has good nutrional properties, is one of the vegetable crops in the Philippines with inadequate information on its inhibition or promotion of sprouting upon application of postharvest treatments.
Keywords: Mindanao studies